Long-term risk of recurrence after discontinuing anticoagulants for a first unprovoked venous thromboembolism: protocol for a systematic review and meta-analysis. Issue 9 (21st September 2017) - Khan, Faizan; Rahman, Alvi; Carrier, Marc; Kearon, Clive; Schulman, Sam; Couturaud, Francis; Prandoni, Paolo; Eichinger, Sabine; Becattini, Cecilia; Agnelli, Giancarlo; Büller, Harry R; Brighton, Timothy A; et al.
Abstract : Introduction: For patients with a first unprovoked venous thromboembolism (VTE), the optimal duration of anticoagulation is a crucial clinical dilemma which has yet to be resolved. The decision to stop anticoagulant therapy (AT) after the initial 3–6 months or to continue AT indefinitely, is primarily governed by the long-term risk of recurrence when treatment is discontinued. This risk however, is not well established, hindering decision making. Methods and analysis: We will conduct a systematic review and a meta-analysis of studies involving patients diagnosed with a first, symptomatic unprovoked VTE or VTE provoked by minor transient risk factors, who have completed at least 3 months of initial AT; and who were followed-up for standardised time intervals of 1, 2, 5, 10 and 20 years (±3 months) after stopping AT. We will search (from inception to January 2017) MEDLINE, Embase and the Cochrane library for randomised controlled trials and prospective observational studies. Two reviewers will conduct all screening and data collection independently. The primary outcome of the rate of recurrent VTE at the standardised time intervals will be calculated for each study from the total number of recurrent events and the corresponding number of patient-years of follow-up. We will use a random-effects model to pool study results and report a weighted estimate of the absolute rate of recurrent VTE (events per 100 patient-years) over standardised time intervals of 1, 2, 5, 10 and 20 years after discontinuing anticoagulants. Ethics and dissemination: Ethical approval is not applicable for this study. Findings from this study will be disseminated through peer-reviewed journal publication as well as relevant national and international conference presentations. PROSPERO registration number: CRD42017056309.